1964
DOI: 10.1139/o64-112
|View full text |Cite
|
Sign up to set email alerts
|

The Alkali-Stable Dinucleotide Sequences in 18 s + 28 s Ribonucleates From Wheat Germ

Abstract: The 2'-0-i~lethyl substitution of ribose residues of ribonucleate chains can give rise to 16 alkali-stable dinucleotides having the general structure NxpNp in which N is any of the four major ribonucleosides and Nx is the 2'-0-methj.1 derivative of any of the four major ribonucleosides. Quantitative data are presented which show that all of these 16 alkali-stable dinucleotides occur in characteristic a~~~o u n t s in alkali hydrolyzates of the 18 S + 28 S ribonucleates from wheat germ. 'The alltali-stable dinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
1

Year Published

1969
1969
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 20 publications
3
40
1
Order By: Relevance
“…The knowledge of the chemical behaviour, structural and biological significance of 2'-O-methylnucleoside residues is still fragmentary. 2'-0-Methylated oligonucleotides are more stable under alkaline conditions than other oligoribonucleotides [3]. The [5], p-chlorophenoxyacetyl for the 5'-hydroxyl group [6], methoxymethylidene for the 2',3'-cis-diol system [7], and benzoyl for the exo-amino group of cytidine.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the chemical behaviour, structural and biological significance of 2'-O-methylnucleoside residues is still fragmentary. 2'-0-Methylated oligonucleotides are more stable under alkaline conditions than other oligoribonucleotides [3]. The [5], p-chlorophenoxyacetyl for the 5'-hydroxyl group [6], methoxymethylidene for the 2',3'-cis-diol system [7], and benzoyl for the exo-amino group of cytidine.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotides containing guanylyl residues only at the 3'-termini were generated by exhaustive enzymatic digestion of highmolecular-weight wheat germ RNA prepared by a modification of the procedure of Singh and Lane (17). RNA as necessary to maintain pH between 7 and 8.…”
mentioning
confidence: 99%
“…Moreover, we have found that the addition of wheat germ RNA to the reaction mixture greatly stimulates the transfer of methyl groups from S-adenosyl methionine to the 2'-oxygen of RNA nucleosides. Wheat-germ ribosomal RNA and alkali-stable dinucleotides were prepared by the method of Singh and Lane (8). Rat liver nuclei were prepared as described (9).…”
mentioning
confidence: 99%
“…Rat liver nuclei were prepared as described (9). DNA was determined with diphenylamine (10 (8). The dinucleotides were then eluted as a second fraction (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation